Biomarkers for febrile urinary tract infection in children - Nader Shaikh; Marcia Kurs-Lasky; Hui Liu; Vinod Rajakumar; Heba Qureini; Isabella O. Conway; Matthew C. Lee; Sojin Lee (Frontiers Media S.A., 2023)
BackgroundThe current reference standard for pediatric urinary tract infection (UTI) screening, the leukocyte esterase (LE) dipstick test, has suboptimal accuracy. The objective of this study was to compare the accuracy of novel urinary biomarkers to that of the LE test.MethodsWe prospectively enrolled febrile children who were evaluated for UTI based on their presenting symptoms. We compared the accuracy of urinary biomarkers to that of the test.ResultsWe included 374 children (50 with UTI, 324 without UTI, ages 1-35 months) and examined 35 urinary biomarkers. The urinary biomarkers that best discriminated between febrile children with and without UTI were urinary neutrophil gelatinase-associated lipocalin (NGAL), IL-1β, CXCL1, and IL-8. Of all examined urinary biomarkers, the urinary NGAL had the highest accuracy with a sensitivity of 90% (CI: 82-98) and a specificity of 96% (CI: 93-98).ConclusionBecause the sensitivity of the urinary NGAL test is slightly higher than that of the LE test, it can potentially reduce missed UTI cases. Limitations of using urinary NGAL over LE include increased cost and complexity. Further investigation is warranted to determine the cost-effectiveness of urinary NGAL as a screening test for UTI.